2021
DOI: 10.1007/s11018-021-01936-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and Creation of a Zeta Potential Reference Material of Particles in a Liquid Medium

Abstract: A comprehensive study to develop and create standard samples of the zeta potential unit of particles in a liquid in accordance with the requirements of GOST ISO 13099-2-2016 in the range of measured values from -150 mV to +150 mV was carried out. The existing standard samples of the zeta potential in Russia and the world have been investigated; an analysis of the applicability of the starting materials and components for the creation of new standard samples is given. Samples based on modifi ed polystyrene lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
1
Order By: Relevance
“…[18][19][20][21] We have shown that L-cysteine (CYS) can simultaneously act as a reducing, capping and gel-forming agent at the simplest mixing of its aqueous solution with silver salts under ambient conditions. [21][22][23][24][25] As a result of the research, we previously found that the surface state and size of the obtained nanoparticles directly determine the ability of the system to form a gel, as well as the properties of the final material: anticancer, catalytic, electrochemical, filmforming.…”
Section: Introductionmentioning
confidence: 97%
“…[18][19][20][21] We have shown that L-cysteine (CYS) can simultaneously act as a reducing, capping and gel-forming agent at the simplest mixing of its aqueous solution with silver salts under ambient conditions. [21][22][23][24][25] As a result of the research, we previously found that the surface state and size of the obtained nanoparticles directly determine the ability of the system to form a gel, as well as the properties of the final material: anticancer, catalytic, electrochemical, filmforming.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, in systems formed by silver nitrite, a stable value of the zeta potential of plus 35with standard deviation is equal to 3 mV is observed for particles at their size of 50 nm [5]. In turn, when initiating the growth of nanoparticles with silver nitrate or silver acetate salts, a time-stable value of the zeta potential of plus 55 mV with standard deviation is equal to 5 mV and plus 69 mVwith standard deviation is equal to 5 mV, respectively, is observed [2,6,7], but the distribution of particles in the systems is polydisperse.…”
Section: Introductionmentioning
confidence: 96%
“…As an analytical method for controlling the quality of products in the chemical, biotechnological and food industries, the zeta-potential allows to determine stability in time of suspensions and emulsions [1]. Currently, the laboratory of metrological support for measurements of parameters of aerosols, suspensions and powdery materials of the Russian metrological institute of technical physics and radio engineering(VNIIFTRI) together with scientists of the Tver State University (TvSU) are developing reference materials of the zeta potential of particles of dispersed systems based on supramolecular systems as precursors [2].…”
Section: Introductionmentioning
confidence: 99%
“…The novelty and advancements accomplished in this work are the study of the physico-chemical properties of CdTe/GSH-QDs and the use of microwave irradiation in their synthesis. These nanocrystals are used in biology and medicine to achieve cellular and biomarker testing [ 12 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%